أبو نصر الفارابي فلسفته ومنهجه - العبيدي , محمود محمد المهدي (Scientific Journal of University of Benghazi, 2022)
The ideology of Al-Farabi represents an important base of reference in the study of philosophical and scientific methodology. This research presents the significance of the methodology in framing philosophical research by addressing some of Al-Farabi's methodological segments as a reminder of the need to resume the study of the Islamic philosophical heritage. This heritage, rich in ideas and subjects, should not be overlooked in all scientific fields and should instead be benefited from, as it is a source of Islamic ideology that deals with multiple sciences with different methodologies and in-depth presentations. This research highlights the issue of methodology according to Al-Farabi as a model depicting the nature of curriculum according to Islamic thinkers. This delicate issue negates the precedence of the European West in this area and emphasizes the contribution of Islamic ideology to the building of a precise methodological rule by which ideas are refined and codified scientifically and coherently. Scientific methodology in Islamic ideology is consistent, inclusive and integrated because it is based on attention to quantity and quality, matter, spirit, purpose and cause, from the perspective of religion. It is a compromise methodology, above all, with the sole aim of consolidating lines of research and their coherence.